ON THE GEOPOLITICAL SITUATION IN THE BLACK SEA REGION: THE CRIMEAN OUTLOOK - A. V. Ishin (Проблемы постсоветского пространства)
In the article difficult geopolitical processes are examined in the Black Sea region. An author spares the special attention the analysis of military-strategic pressure of evroatlantic block, its tool and mechanisms, «Turkish» and «Ukrainian» factors.